Impotent Masculinities in Frank Wedekind’s «Erdgeist» (Studia theodisca, 2013)
For most of recorded history, the study of impotence fell under the purview of healers. This changed in the late nineteenth century, however, as the works of avant garde artists like the German dramatist and social critic Frank Wedekind ushered analyses of this malady into public discourse. In looking first at conditions in Europe during Wedekind’s time and then tracing the history of impotence from the Ancient Chinese up to Wedekind’s day, this article investigates how Wedekind’s representations of impotence emblematized not only his own personal afflictions but a greater cultural malaise.